2004
DOI: 10.2190/78uq-5nmw-7yld-tfwv
|View full text |Cite
|
Sign up to set email alerts
|

The Attainment of Important Health Goals Throughout Adulthood: An Integration of the Theory of Planned Behavior and Aspects of Social Support

Abstract: This research integrates the Theory of Planned Behavior (TPB) with aspects of social support and explores the utility of variables within each model in predicting the attainment of important health goals. Incorporating an idiographic methodology, 290 respondents ranging in age from 27 to 87 years were administered a postal survey and completed a brief follow-up telephone survey months later. The postal survey included measures of respondent's most important health goals, attitudes, motivation to comply with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
3
21
0
Order By: Relevance
“…Indeed, in a study with a large community-based sample, Courneya et al showed that social support was a stronger predictor of exercise intention than subjective norm. Similarly, VonDras and Madey (2004) showed that the social support offered by a close friend or family member was more important in predicting behavioural intentions in the health domain, than subjective norm. Symons Downs and Hausenblas (2005) agreed that social support may be a stronger predictor than subjective norm, but indicated that the data is still insufficient to be able to draw firm conclusions on this issue.…”
Section: Subjective Normmentioning
confidence: 97%
“…Indeed, in a study with a large community-based sample, Courneya et al showed that social support was a stronger predictor of exercise intention than subjective norm. Similarly, VonDras and Madey (2004) showed that the social support offered by a close friend or family member was more important in predicting behavioural intentions in the health domain, than subjective norm. Symons Downs and Hausenblas (2005) agreed that social support may be a stronger predictor than subjective norm, but indicated that the data is still insufficient to be able to draw firm conclusions on this issue.…”
Section: Subjective Normmentioning
confidence: 97%
“…According to the TPB model, whether or not an individual intends to perform a specific behaviour depends upon personal attitudes, desire to adhere to social norms, and perceptions regarding degree of control over performance (VonDras and Madey, 2004). Under these assumptions, an older adult's participation in a physical activity (behaviour) is determined by the individual's personal beliefs concerning the exercise (attitudes), perception of social acceptability or pressure from others towards the activity, and subjective evaluation of the degree of ease or difficulty in performing the activity.…”
Section: Social Support and Older Adults' Leisure Lifestylesmentioning
confidence: 99%
“…VonDras & Madey (2004) conclude the theory of planned behavior components and social support by close family or friends offer an integrated model for health interventions. Therefore the education plan was designed to offer the patient and family instruction related to the three determinants of the theory of planned behavior.…”
Section: Designing a Falls Prevention Patient And Family Education Planmentioning
confidence: 81%
“…Social support theory and the quality of one's social support has also been studied extensively in the health care field and found to be a powerful factor for individuals meeting health related goals (VonDras & Madey, 2004). Social support theory identifies how interpersonal relationships can influence the health behavior of others in both a positive or negative manner.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation